Presbyterian teenage community: habits and values - Gabriel, Oldrey Patrick Bittencourt; Vieira, Lenamar Fiorese (Journal of Physical Education (Maringá), 2008)
The main purpose of this study was to investigate values and habits of the First Presbyterian Independent Church (1st</spu>. PIC) in the city of Maringá, state of Paraná, Brazil and its influence in it teenage community leisure activities. A questionnaire with objective and discursive questions was used for investigating. Describing statistics and categorical-type contents analysis were used to analyze the data. The results showed that the teenagers have God, family, church, friends and health as their lives’ main values, and these values were transmitted mainly by their families and church. Most of the teenagers polled declared to live according to these values; As for their habits, they showed interest for more practical issues, such as friendship, music, the church, family and sports. Leisure activities were linked by them to rest and pleasure, being the campings pointed as the best way to learn the values of their church. Thus we may conclude that the teenagers values from this church are mostly coherent with their daily habits, being church and family the most important factors for transmitting and keeping these values in the teenagers lives. Campings were a peculiar moment in the values transmission motivational aspect.